Sexual and gender minority cultural humility training for oncology settings: An example of iterative adaptation and implementation - Kamen, Charles S.; Reichelt, Melhaney; Dadgostar, Porooshat; Alpert, Ash B.; Doucette, Christopher; Vaughan, Phillip; Keuroghlian, Alex S.; Yousefi-Nooraie, Reza (Frontiers in Health Services, 2022)
Background Multiple national organizations recommend that cancer care providers and oncology practices be responsive to the needs of sexual and gender minority (SGM) patients. Oncology practices have attempted to incorporate this recommendation through SGM-focused cultural humility training interventions. It is unclear how best to adapt and implement such training across practices. This manuscript outlines one process for adapting a widely-used SGM training from The Fenway Institute to the context of oncology settings using the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME) model. Methods We conducted training sessions in two oncology care settings: a breast oncology center and a radiation oncology department. Subsequently, we conducted in-depth interviews with the three trainers involved in adapting The Fenway Institute's training to these two practices. Two independent investigators coded the interviews using components of the FRAME model as an analytic guide. Results Training team members described the mechanisms by which FRAME adaption occurred both proactively and reactively; the importance of involving SGM-identified trainers of diverse backgrounds as well as champions from within oncology practices in which trainings were conducted; the importance of adapting both the context and content of training to be relevant to oncology audiences; and the ways in which fidelity to the core principles of improving health care for SGM patients was maintained throughout the process. Discussion SGM cultural humility training for oncology providers and staff must undergo iterative adaptation to address the political and social context of specific practice environments and advocate for broader institutional culture change to achieve responsiveness to SGM health needs.